THE INTRACELLULAR SIGNALING MOLECULE DARPP-32 IS A MARKER FOR PRINCIPAL NEURONS IN THE CEREBELLUM AND CEREBELLUM-LIKE CIRCUITS OF ZEBRAFISH. - Lena Robra; Vatsala Thirumalai (Frontiers in Neuroanatomy, 2016)
The dopamine and cAMP regulated phosphoprotein of apparent molecular weight 32 kDa (Darpp-32) is an inhibitory subunit of protein phosphatase-1 (PP-1). Darpp-32 activity is regulated by multiple ligand-activated G-protein coupled receptors. This protein is coded for by the phosphoprotein protein phosphatase -1 regulatory subunit 1b (ppp1r1b) gene. Here, we provide experimental evidence for the presence of multiple isoforms of ppp1r1b in zebrafish. We show that these isoforms are differentially expressed during development with the full-length isoform being maternally deposited. Next, with a custom polyclonal antibody generated against the full-length protein, we show that in the adult, Darpp-32 is strongly expressed in principal neurons of the cerebellum and cerebellum-like circuits. These include Purkinje neurons in the cerebellum, Type-I neurons in the optic tectum, and crest cells in the medial octavolateralis nucleus (MON). We confirmed the identity of these neurons through their colocalization with Parvalbumin 7 immunoreactivity. Darpp-32 is seen in the somata and dendrites of these neurons with faint staining in the axons. In all of these regions, Darpp-32-immunoreactive cells were in close proximity to tyrosine hydroxylase immunoreactive puncta indicating the presence of direct catecholaminergic input to these neurons. Darpp-32 immunoreactivity was seen in Purkinje neurons as early as 3dpf when Purkinje neurons are first specified. In sum, we show that Darpp-32, a signaling integrator, is a specific marker of principal neurons in the cerebellum and cerebellum-like circuits in zebrafish.